A Process Reference Model for Managing Living Labs for ICT Innovation: A proposal based on ISO/IEC 15504 - Fernández Del Carpio, Alvaro (2013)
Living Labs are innovation infrastructures where software companies and research organizations collaborate with lead users to design and develop new products and services. There is not any reference model related to the processes or practices to manage a living lab. This article presents a reference model to manage effectively the synergies of software companies with the other stakeholders participating in a living lab. The article describes the approach used to create the reference model through the analysis of a multiple case study considering six living labs and discusses the lessons learned during the creation of the process reference model.